Hyperglycemia may increase deep vein thrombosis in trauma patients with lower limb fracture - Liu, Xiaojie; Li, Tiajun; Xu, Hui; Wang, Chunhua; Ma, Xiaojun; Huang, Hui; Hu, Yanling; Chu, Haichen (Frontiers in Cardiovascular Medicine, 2022)
A previous study illustrated that diabetes was associated with prothrombotic states and thrombotic events. This study aimed to examine the association of preoperative glucose with deep vein thrombosis (DVT) in trauma patients accepted with fracture surgery. Data from 1591 patients who underwent fracture surgery from January 2017 to March 2022 at the Affiliated Hospital of Qingdao University were queried from institutional electronic medical records. Patients were divided into 2 groups according to whether they experienced DVT or not, including 138 patients who experienced DVT and 948 control patients. The primary outcome was DVT. Multiple logistic regression analyses were performed. A receiver operating characteristic curve was generated. Age, D-dimer, preoperative RBC, and preoperative glucose, were independent predictors of DVT by multiple logistic regression. The last two categories of d-dimers (≥960, <2102, ≥2102 ng/ml) increased the odds ratio by 4.215 times (95% confidence interval [CI]1.820–9.761) and 7.896 times (95% CI 3.449–18.074) for DVT, respectively, compared with the lowest reference category of d-dimers (<490 ng/ml). While the diabetes state was not associated with DVT, the AUC of preoperative glucose was 0.605. Hyperglycaemia (≥6.1, <7.0 mmol/l) increased the odds of DVT by 1.889-fold (95% CI (1.085, 3.291); p < 0.0001) compared with euglycaemia (<6.1 mmol/l). There is an association between preoperative hyperglycaemia and DVT in patients with lower limb fracture. Several specific management modalities were associated with controlling hyperglycaemia, which offers targets for future quality improvement.